Development, profitability and employment-enhancing effect of household and private pigeon breeding - Jilly, Bertalan (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The purpose of squab producing is to supply the retail trade with ready-to-cook meat pigeons meeting the highest requirements of customers. To achieve this, more emphasis should be laid on modern keeping and breeding methods, and on acquainting future breeders with meat pigeons requiring intensive technologies, developed through purposeful breeding activities, and on multiplying the breeding population. It is also vital to implement an organised system of purchasing young pigeons for processing and distributing on an industrial scale. Ten times the amount of 1st class quality ready-to-cook squab (0.45-0.55kg/pigeon) currently produced in Hungary could be exported to Western European and Arab markets. Low investment production of utility pigeons on small farms may help to provide farming families with meat, while any surplus production may be sold. Producing large amounts of 1st class squab may necessitate the full-time employment of a worker, bringing some improvement in the national employment situation and an increase in the income of the families. Those who are interested in producing squab can be helped efficiently by training courses, while those interested in other phases of the processes of production can be aided by permanent consultation with or information from extension services. This would be useful for all the parties involved in a well-organised, mutually beneficial cooperation.
Keywords: squabs to the market; opportunities for improving production; form of subsidies; low investment needs; high profitability; export product with high demand